Development Timelines of Innovative Drugs in China: A 15‐Year Cross‐Sectional Analysis of Characteristics and Influencing Factors - Meimei Xu; Chenpeng Wang; Xinying An (Clinical and Translational Science, 2026)
ABSTRACT Timely development and approval of innovative drugs are essential for patient access and public health. China has implemented regulatory reforms, including priority review and conditional approval, to accelerate drug development. We conducted a cross‐sectional study of 232 innovative drugs, comprising chemical drugs, biologics, and traditional Chinese medicines ( TCMs ), approved by the National Medical Products Administration during 2010–2025. Development timelines for 227 drugs were analyzed using generalized linear models with a gamma distribution and log link to assess associations with drug type, regulatory pathways, orphan drug status, reform stage, indication, primary endpoint duration, and sample size. Median total development time was 6.94 years ( IQR , 4.85–9.97), with biologics having the shortest duration (5.14 years) and TCMs the longest (10.22 years). Drug type and conditional approval were primary variables associated with total development time. Conditional approval was associated with shorter total development time among oncology drugs (relative mean ratio [ RMR ] = 0.66, p < 0.001), with a significant interaction by indication ( RMR = 2.08, p < 0.001). Among drugs not receiving conditional approval, clinical development time was longer in later reform stages by up to 52%, whereas marketing application review time decreased in later reform stages overall, with a 64% reduction in Stage III ( RMR = 0.36, p < 0.001). Priority review and conditional approval were associated with 26% and 28% reductions in review time, respectively (both p < 0.05). These findings suggest heterogeneous associations of China's regulatory reforms across pathways and therapeutic areas, consistent with differential contributions of administrative acceleration and evidentiary modification to development timelines.